The van der Waals Epitaxy of High‐Quality N‐Polar Gallium Nitride for High‐Response Ultraviolet Photodetectors with Polarization Electric Field Modulation. (20th October 2021) - Chen, Yang; Shi, Zhiming; Zhang, Shanli; Ben, Jianwei; Jiang, Ke; Zang, Hang; Jia, Yuping; Lü, Wei; Li, Dabing; Sun, Xiaojuan
Abstract: High‐quality and polarity‐controlled III‐nitride is crucial for realizing high‐performance and new types of device designs with rich functionalities, but there are still many difficulties for obtaining N‐polar III‐nitrides till now. In this work, the van der Waals epitaxy of high‐quality N‐polar gallium nitride (GaN) is reported by innovatively inserting a thin MoS2 layer. Due to the remission of thermal and lattice mismatch by the week van der Waals force in 2D MoS2 insert layer, the N‐polar GaN exhibits high crystalline quality and reduced residual stress. The proposed atom deposition kinetics for the van der Waals epitaxy of the polarity‐controlled aluminium nitride nucleation layer and GaN epilayer on the MoS2 lighten the great potentiality for the application of similar 2D materials. The ultraviolet photodetector based on N‐polar GaN possesses over seven times' response higher than that of the Ga‐polar one, which is both beneficial from the high crystalline quality and efficient polarization electric field control of the N‐polar GaN. Present work provides a new strategy for the polarity control of high‐quality III‐nitrides by the van der Waals epitaxy with a novel 2D insert layer, which would be also extended in other optoelectronic and electronic devices. Abstract : The van der Waals epitaxy of N‐polar GaN is achieved by innovatively inserting a 2D MoS2 layer, and the atom deposition kinetics for polarity modulation are proposed by first‐principles calculations. The ultraviolet photodetector based on N‐polar GaN and graphene junction possesses seven times enhancement in responsivity, which benefits from the high crystalline quality and modified polarization electric field.